Implementation of Problem-Based Learning Model to Improve Mathematical Problem-Solving Skills of Praya Timur Middle School Students - Lalu Aji Muliardi Akbar; Nailu Salma (LOGIKA: Jurnal Pendidikan Matematika, 2025)
This study aims to determine the effect of the implementation of the Problem-Based Learning (PBL) model on the mathematical problem-solving abilities of eighth-grade students at SMP Negeri 2 Praya Timur. The research method used was a quasi-experimental with a pretest-posttest control group design. The subjects were 60 students divided into an experimental class and a control class. The research instrument was a mathematical problem-solving ability test whose validity and reliability had been tested. The results showed a significant increase in problem-solving abilities in students who learned with the PBL model compared to students who learned using conventional methods. The implementation of PBL helped students be more active, think critically, and be able to connect mathematical concepts with real-world situations. These findings recommend the use of PBL as an alternative mathematics learning strategy in secondary schools.